GAMBARAN CEDERA KEPALA DENGAN KOMPLIKASI PERDARAHAN EPIDURAL DI RSU DOKTER SOEDARSO PONTIANAK 1 JANUARI 31 DESEMBER 2010 - ., Muhammad Azwar (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Head injury had a high incidents in the world. Head injury especially happened in the productive age group. Epidural haemorrage is the complication of head injury and one of the emergency case in neurosurgery, led to made disability and death. The mortality rate of epidural haemorrage was vary between 5-50% depend on the level of Glasgow Coma Scale (GCS). Objective: To find the case of head injury with epidural haemorrage at RSU Dokter Soedarso Pontianak in 2010. Methodology: A descriptive observational study were taken from patient medical records. Result: There were 55 cases included as the samples. Most age group were the result who had the head injury with epidural haemorrage were the second decade (age 11-20 years old) as much as 49.09%, followed by third decade (age 21-30 years old) as much as 25.45%. The male to female ratio is 4.5:1. Road Traffic Accident (RTA) is the main causes of head injury with epidural haemorrage as much 89.09%. Mild head injury (GCS 13-15) is the most common level as much as 25 cases (48.08%). The non Golden Period operated group of epidural haemorrage are 44 cases (84.62%). Conclusions: The second dacade age group dan male are the most common, the main causes is RTA, the mild head injury is the most common and the most of the cases are the non Golden Period operated group.Keywords: Head injury, epidural haemorrage